Arsenicosis in risk household: Situation, analysis and mitigation ( A case study in Santipur VDC, Rautahat, Nepal). - Adhikari, Hom Jyoti (2006)
ABSTRACT: ABSTRACT Arsenic contamination in drinking water has been one of the biggest epidemics of the global concern including Bangladesh, India and Nepal. The general objective of the study is to sketch out the impacts of arsenic contamination on human health through drinking water in Santpur VDC, Rautahat District, Nepal. the study was of cross-sectional types and the tools and techniques applied were the Questionnaires, direct observation, Interview Arsenic Field Test Kit (ENPHO), WHO-Flow Chart, Litholog Analysis, Arsine Generator Method and statistical tools (x2-test at 95% confidence level). In the present study, 124 people were examined from 36 risk households who used to drink water from 42 tube wells. The overall prevalence of arsenicosis symptomatic patients among the risk household of Santpur VDC was found to be 15.3% (19 out of 124). The prevalence of Melanosis in trunk was 84.21% (16 out of 19), and keratosis in sole and palm was 15.79% (3 out of 19). The highest prevalence of arsenicosis was 22.8% (13 out of 57, x2=4.553, p< 0.05) in males, 29.09% (16 out of 55, x2= 14.518, p<0.05) in illiterate people, 17.50% (18 out of 103, x2= 2.172, p> 0.05) in the poor, 51.72% (15 out of 29, x2=152.792, p<0.05) in agricultural workers. Arsenicosis was present in the people after the age of 40 years. Thirty-one wells (72.09%) were contaminated by more than 10 ppb of arsenic being highest tube wells (15) in the ranges of 17-33 feet with statistically insignificant (x2=10.984, p>0.05). All positive patients (19 out of 19, 100.0%) had been drinking arsenic contaminated water for 1.5-25 years being 1.5 years by one patient and 5-25 years by 18 patients. Positive correlation (R2=0.9741) was found between ENPHO arsenic kit test and laboratory method (Arsine Generator). Management strategy for combating the severity of arsenic problem should be the development of groundwater through deep aquifers. Proper investigations need to be carried out evaluate the various clinical manifestations of arsenicosis. Keywords: Arsenic contamination, Arsenicosis, risk household